Image deformation with length‐preserving feature curves. Issue 22 (1st October 2013) - Zhou, X.J.
Abstract : Image deformation techniques have been widely used in the entertainment industry, animation and medical imaging. Motivated by the fact that the lengths of some feature curves should remain constant during the deformation, an image deformation method is proposed with length‐preserved feature curves. Intrinsic representation of the curves is used to achieve length‐preserving curve deformation, and then the deformation of the image is driven by the deformation of the feature curves.